Evaluation in natural science subjects in the current context of Slovak education - Orosová, Renáta; Ganajová, Mária; Szarka, Katarína; Babinčáková, Mária (Scientia in educatione, 2019)
Evaluation has a considerable influence on the personality of the pupil, on his or her learniong process and ultimately also on creating his/her relationship to the content of a school subject. The PISA 2015 National Administration (NUCEM, 2017) indicates a drop in the performance of pupils in natural science literacy, with the largest risk group of pupils being pupils of primary schools and secondary vocational schools without baccalaureate. The question facing the educators is how to reverse this negative trend. On the basis of substantial research one of the options appears to be a formative assessment which has a qualitative character. The authors of the paper sought to establish the current status of evaluation tools in the teaching of natural science subjects. They used the questionnaire as a method of quantitative research. The paper presents partial research findings that point to the considerable dominance of using tools of summative assessment over tools of formative assessment. The respondents were teachers of natural science subjects in primary and secondary schools in Slovakia.